Transcendentalism and the problem of literary vision in nineteenth-century America - Kohler, Michelle, 1974- (The University of Alabama Press, 2014)
"Miles of Stare explores the problem of nineteenth-century American literary vision: the strange conflation of visible reality and poetic language that emerges repeatedly in the metaphors and literary creations of American Transcendentalists"--